Cabaran Penggunaan Teknologi Internet of Things (IoT) Dalam Industri Pembinaan di Malaysia - Zakaria, Zairus Fadela; Yahya, Mohd Yamani (Research in Management of Technology and Business, 2023)
The Internet of Things (IoT) is a network of technologies that use sensors, software, and other technologies to connect and exchange data with other devices and systems over the internet. However, several issues arise from the use of IoT, such as a lack of exposure to new technologies. Traditional construction methods are usually more appealing to older people in the construction industry than more modern and technological methods. As a result, the objectives of this study were to examine the types of IoT technology used in the Malaysian construction industry, the frequency with which IoT technology is applied in the Malaysian construction industry, and the challenges associated with using IoT in the Malaysian construction industry. This study employed a quantitative approach, with questionnaires distributed to 66 G7 contractors in Johor Bahru as respondents. Data is analysed using descriptive statistics and the Statistical Package for Social Science (SPSS) software. The study discovered that the main types of IoT used in the Malaysian construction industry are Building Information Modeling (BIM). While the main challenge of using IoT in the Malaysian construction industry was a lack of skilled manpower, such as a lack of knowledge and skills in handling IoT technology, as well as a lack of training and courses to improve employees’ professional skills. Finally, it is hoped that the contractor will take an open role in raising community awareness about the use of IoT in the Malaysian construction industry, as well as steps to improve the use of IoT in the Malaysian construction industry.